Numerical simulation and experimental study of filling process of micro prism by isothermal hot embossing in solid‐like state. Issue 6 (20th March 2017) - Sun, Jingyao; Wu, Daming; Liu, Ying; Dai, Le; Jiang, Chong
Abstract: Filling process of micro prism array by isothermal hot embossing in solid‐like state (IHESS) with different mold temperature, pressure, and holding time were simulated by DEFORM. Polymethyl methacrylate (PMMA) samples processing by IHESS were tested to validate the numerical simulation results and select the best processing condition. The reliability of simulation was tested quantitatively and qualitatively by comparing the cross‐profile and its developing trend separately. It was found that the cross‐profiles from the simulations and experiments were in high agreement. The simulated and experimental developing trends of cross‐profiles were also the same. These results proved the reliability of simulation and its guidance to the experiments. In order to show the advantages of IHESS, a brief introduction and comparison of IHESS and traditional hot embossing were made.